The efficacy of hydrothermally obtained carbonated hydroxyapatite in healing alveolar bone defects in rats with or without corticosteroid treatment - Marković Dejan; Jokanović Vukoman; Petrović Bojan; Perić Tamara; Vukomanović Biserka (Vojnosanitetski Pregled)
Background/Aim. Autogenous bone grafting has been the gold standard in clinical cases when bone grafts are required for bone defects in dentistry. The study was undertaken to evaluate multilevel designed carbonated hydroxyapatite (CHA) obtained by hydrothermal method, as a bone substitute in healing bone defects with or without corticosteroid treatment in rats as assessed by histopathologic methods. Methods. Bone defects were created in the alveolar bone by teeth extraction in 12 rats. The animals were initially divided into two groups. The experimental group was pretreated with corticosteroids: methylprednisolone and dexamethasone, intramuscularly, while the control group was without therapy. Posterior teeth extraction had been performed after the corticosteroid therapy. The extraction defects were fulfilled with hydroxyapatite with bimodal particle sizes in the range of 50-250 μm and the sample from postextocactional defect of the alveolar bone was analyzed pathohystologically. Results. The histopatological investigations confirmed the biologic properties of the applied material. The evident growth of new bone in the alveolar ridge was clearly noticed in both groups of rats. Carbonated HA obtained by hydrothermal method promoted bone formation in the preformed defects, confirming its efficacy for usage in bone defects. Complete resorption of the material’s particles took place after 25 weeks. Conclusion. Hydroxyapatite completely meets the clinical requirements for a bone substitute material. Due to its microstructure, complete resorption took place during the observation period of the study. Corticosteroid treatment did not significantly affect new bone formation in the region of postextractional defects. [Projekat Ministarstva nauke Republike Srbije, br. 172026]